Liquid chromatography-tandem mass spectrometry method for quantification of gentamicin and its individual congeners in serum and comparison results with two immunoanalytical methods (fluorescence polarization immunoassay and chemiluminiscent microparticle immunoassay) - Brozmanova, Hana; Urinovska, Romana; Safarcik, Kristian; Vsiansky, Frantisek; Kacirova, Ivana; Grundmann, Milan (Clinica chimica acta; international journal of clinical chemistry, 2021)
BACKGROUND: Total gentamicin is a sum of five congeners C1, C1a, C2, C2a and minor C2b, which differ from each other in their methylation on the purpurosamine ring. Liquid chromatography with mass detection (LC-MS/MS) and specified calibration material enables the concentration of total gentamicin and its individual congeners to be analysed. METHODS: 50 µL serum was precipitated with acetonitrile in the presence of 0.5 mol/L formic acid. A RP BEH C18 1.7 µm 2.1x50 mm column maintained at 30 °C and tobramicin as the internal standard were used. Mass detection was performed in positive electrospray. The gentamicin results were compared with fluorescence polarization immunoassay (FPIA) and chemiluminiscent microparticle immunoassay (CMIA). Passing-Bablock regression analysis and Bland-Altman analysis were used. RESULTS: Calibration curves for individual gentamicin congeners were linear with correlation coefficients between 0.997 and 0.998. Recovery was 91.6-102.0% and the coefficients of variation 1.4-8.4%. The total gentamicin concentration was compared with immunoassay FPIA (LC-MSgen = 0.9798xPFIAgen) and CMIA (LC MSgen = 0.9835xCMIAgen) both with significant correlation (p < 0.001). CONCLUSION: The LC-MS/MS method is fast and precise and can be applied to routine TDM in patients. Comparing it to immunoassays makes it possible to measure concentration of gentamicin congeners, which may be important in the case of their different pharmacokinetics.
Keywords: imunoanalýza; Reproducibility of Results; reprodukovatelnost výsledků; Immunoassay; gentamiciny; LC-MS/MS; Total gentamicin concentration; Chemiluminiscence microparticle immunoassay; Therapeutic drug monitoring; Humans; Gentamicins; Tandem Mass Spectrometry; fluorescenční polarizační imunologické testy; chromatografie kapalinová; Fluorescence polarization immunoassay; tandemová hmotnostní spektrometrie; Fluorescence Polarization Immunoassay; Chromatography, Liquid; lidé